2020
DOI: 10.1055/s-0040-1718469
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endodontic Instrumentation on Surface Roughness of Various Nickel-Titanium Rotary Files

Abstract: Objectives The aim of the present study was to evaluate the surface roughness (SR) of various nickel-titanium (NiTi) rotary endodontic instruments (ProTaper Next [PTN], WaveOne Gold [WOG], and ProTaper Gold [PTG]) before and after root canal instrumentation. Materials and Methods For each type (PTN, WOG, and PTG), the endodontic instrumentation was performed using extracted mandibular molar teeth’s curved mesial root canals (curvature: 20–40 degrees) after determining the working length. Each NiTi file was cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 54 publications
3
16
0
1
Order By: Relevance
“…In this study there were no fractured files. This result is in agreement with previous studies that state that martensitic phase alloys are more resistant to fractures in curved ducts [23,24,28].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study there were no fractured files. This result is in agreement with previous studies that state that martensitic phase alloys are more resistant to fractures in curved ducts [23,24,28].…”
Section: Discussionsupporting
confidence: 93%
“…In addressing the quality of endodontic teaching, dental schools have undergone changes to improve the teaching-learning process for students [13], specifically pre-clinical instrumentation practices. There are universities that continue to instruct in the stepback technique using steel files (K-files) [4,14] which, being more rigid, can lead to errors during the procedure [15,16]; on the contrary, other universities have chosen to teach undergraduate students to use rotary instrumentation with nickel-titanium (NiTi) instruments [8,[17][18][19] because they allow the performance of RCTs to be achieved in a fast and predictable way [3,11,16,20,21], presenting lower complication rates [10,22] due to the fact that these rotary instruments cause fewer errors in the root canal preparation compared to manual files [23] because they are more flexible [24]. With NiTi instruments, it is possible to improve the student's experience in their preclinical training [10] because, by performing these treatments more quickly, the number of practice attempts is increased, and an increase in the repetition of a procedure has proven to be very useful in preparing students in the acquisition of acceptable preclinical skills that will translate into better preparation and the optimization of their future professional practices [4,11,22,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elanghy et al reported a statistically significant ( p < 0.001) higher cyclic fatigue resistance of ProTaper Next and ProTaper Gold compared to conventional NiTi alloys of TRUShape and ProTaper Universal NiTi endodontic rotary systems [ 46 ], and Uygun et al reported similar results when comparing ProFile Vortex Blue and ProTaper Next with the conventional NiTi alloy of ProTaper Universal [ 47 ]. These results agreed with those obtained in the present study and highlight the relevance of the alloying elements in the allotropic transformation of the crystalline structure of the NiTi alloy, which in turn influences the physical and mechanical properties of the endodontic rotary files [ 47 ]. Titanium is an allotropic metal which can present two crystalline structures: compact hexagonal (α or austenite) and body-centered cubic (β or martensite).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that it is conceivable to reuse the instruments. 8,10,12,13 Yared et al in a simulated clinical study found that up to four molar teeth could be prepared using the same rotary instrument without the fear of instrument fracture. 14 Parashos et al reported that the incidence of fracture of rotary instruments may indeed be lower than that for stainless steel manual files, and the reasons for fracture of rotary instruments are intricate and multifactorial.…”
Section: Discussionmentioning
confidence: 99%